Olfactory identification in LRRK2 G2019S mutation carriers: a relevant marker?. (September 2014) - Saunders‐Pullman, Rachel; Mirelman, Anat; Wang, Cuiling; Alcalay, Roy N.; San Luciano, Marta; Ortega, Robert; Raymond, Deborah; Mejia‐Santana, Helen; Ozelius, Laurie; Clark, Lorraine; Orr‐Utreger, Avi; Marder, Karen; et al.
Abstract Objective Olfactory impairment is a potential marker for impending phenoconversion to Parkinson disease (PD) that may precede the development of disease by several years. Because of low specificity, it may be of greater predictive value in those with genetic mutations and its potential as a marker for developing LRRK2 PD should be evaluated. Methods We examined olfactory identification in 126 LRRK2 G2019S mutation carriers with PD, 125 mutation carriers not manifesting PD, 126 noncarriers with idiopathic PD, 106 noncarrier family members without PD, and 35 unrelated controls. We compared olfactory performance and performed mixture modeling to identify possible subgroups of olfactory performance in LRRK2 PD and nonmanifesting carriers. Results Adjusting for sex, age, cognitive score, site, and smoking history, LRRK2 PD had better olfactory scores compared to idiopathic PD (mean olfaction difference: −3.7, P < 0.001), and both LRRK2 PD and idiopathic PD had worse olfaction than controls (−12.8, −9.1, both P < 0.001). LRRK2 PD were less likely to be hyposmic than idiopathic PD (54.8% vs. 80.2%, P < 0.001). Nonmanifesting carriers and noncarrier family members did not differ. Mixture model analysis identified three classes in the LRRK2 PD and nonmanifesting carriers, suggesting that there are subgroups with poor olfactory identification in both LRRK2 PD and nonmanifesting carriers. Interpretation Therefore, olfactory identification deficit is less likely to be an obligate feature in LRRK2 PD than idiopathic PD, and while a relevant marker in some, a subset of carriers who eventually phenoconvert may proceed directly to PD without prior impaired olfaction.